Corporate governance and insider trading: evidence from Malaysia - Ahmad Kamal, Siti Aisyah; Hasnan, Suhaily; Mohd Nasarudin, Ahmad Fawwaz (Academic Research Publishing Group, 2018)
The collapse of prominent companies coupled with the increasing number of lawsuits against the directors of the companies for wrongdoing has raised concerns with insider trading activities. Insider trading does cause significant market reaction, whereby the insiders are able to earn significant cumulative abnormal returns for both purchases and sales. However, studies on the factors influencing insider trading are relatively scarce. This study aims to examine the factors that influence insider trading activities. Specifically, this study examines the relationship between four corporate governance factors, namely, board independence, board size, executive compensation and ownership concentration and insider trading activities in public listed companies in Malaysia. This study evinces that board size and executive compensation significantly influence insider purchases. On the other hand, significant market reaction caused by insider sales may be explained by other factors. Therefore, future studies could be carried out on other factors that may influence opportunistic insider sales. This study also found evidence against the semistrong form Efficient Market Hypothesis theory that suggests insiders cannot earn abnormal returns in a semi-strong efficient market using public information